Copper-catalyzed C–H acyloxylation of 2-phenylpyridine using oxygen as the oxidant. Issue 29 (3rd May 2018) - Wang, Feifan; Lin, Zhiyang; Yu, Weisheng; Hu, Qingdong; Shu, Chao; Zhang, Wu
Abstract : A copper catalyzed direct o -acyloxylation of 2-phenylpyridine with various carboxylic acids using oxygen as oxidant has been developed. Abstract : An efficient copper-catalyzed direct o -acyloxylation of 2-phenylpyridine with carboxylic acids using oxygen as the oxidant has been developed. Various acids including aromatic acids, cinnamic acids and aliphatic acids are effective acyloxylation reagents and provide the desired products in moderate to excellent yields. The reaction proceeds well under an oxygen atmosphere, making this method potentially practical.